Resíduos orgânicos: uma alternativa sustentável na supressividade de fusarium em quiabeiros para a agricultura familiar maranhense. - Veras, Márcia de Sousa (2006)
This paper verify the changing effect challenge by organic residues in the supressiveness of the Fusarium oxysporum f. sp. vasinfectum (Atk), cause agent of the fusarium wilt or fusariose in the okra (Abelmochus esculentus L.). The organic residues utilized in this study were: peel of cassava Manihot esculenta Crantz, pie of Orbignya falerata Mart., sugar cane pulp Saccharum officinarum L., Cymbopogon nardus L., Azadirachta indica Juss.A previous survey was made about handling and production of the cultivation under study. The samples of the organic residues were submitted to the physical chemistry and microbiological analyses. As assessment was made about the inoculation observance for 15 days with base in experimental randomized factual arranged 2 x 2 (two cultivars, two methods root wounded and deeping), and still, had with cultivars the cultivars IAC-47 e Valença, conducted in greenhouse in vases with capacity 1 dm3 . Assessment continued on 10 treatment procedures and 5 repetitions, the experimental unit consisted of a vase with two plants. The statistic program STAT was used. There was an evaluation on the affect over wet about micelial increase of F. oxysporum f. sp. vasinfectum. Using in, this form, the concentrations (2, 4, 6, 8, 10 %). The randomized factual design arranged with factorial 5 x 6, were five residues and six concentrations, and five repetitions. The bacteria and total fungus quantities were observed for each residue and the number of total bacteria colonies after 24 hours, and total fungus as for identification in total fungus for 72 hours, after inoculation. The organic residues were also evaluated in vivo using the greenhouse with different concentrations (0, 20, 40, 60, 80, 100 g.kg-1 de solo) and different periods the incubation of the organics residues (0, 15, 30, 45 and 60 days), the autoclaved soil substract and maintained the cultivar IAC-47 with two plants by vase. The randomized experimental design arranged was conducted with six treatments and five repetitions. The assessment was made within 15 days after the inoculation based on notes scale and internal symptoms and the medium compared by Tukey Test by 5 % of probability. Finally, the evaluated was done on the organic residues from the best concentration and incubation period verified prior analyses. The evaluated was conducted on autoclaved soil and the cultivar IAC-47 in two plants per vase. The experimental outline was wholly done with a simple treatment and five repetitions. The evaluation procedure was done 20 days after the inoculation based in notes scale and internal symptoms. The okras production in the Metropolitan region of São Luis confirmed important production of 15 tons. in local community. According to the results in physical chemistry the organic residues, sugar cane pulp Saccharum officinarum, Cymbopogon nardus and Azadirachta indica, showed coherence among themselves. In the microbiological survey on extracts, bacteria number was larger on extract Cymbopogon nardus, being in smaller proportion on Azadirachta indica. Among the fungus species the following was observed: Aspergillus niger, Aspergillus flavus, Rhizoctonia sp., Penicillium spp., ond Rhizopus stolonifer. The inoculation methods showed no important difference on patogenity, o ISO-7 outstood in such a way that it was preferred in conducting on other experiments. The effect in vitro of wet was significant the micelial growth of soil F. oxysporum f. sp. vasinfectum to all residues especially to wet extract Cymbopogon nardus. With regards, to results in vivo, the concentration 20 g.kg-1 was more effetive on the control evident on the Azadirachta indica as being effective controlleux the fusariose. It‟s too essential to the biological control is an alternative in the control of inhabitant fungus of soil as it was verified regarding the F. oxysporum f. sp. vasinfectum.